2021
DOI: 10.3389/fonc.2021.749137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Machine Learning-Based Ultrasomics in Preoperative Differentiation Between Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma: A Multicenter Study

Abstract: ObjectiveThis study aims to explore the clinical value of machine learning-based ultrasomics in the preoperative noninvasive differentiation between hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC).MethodsThe clinical data and ultrasonic images of 226 patients from three hospitals were retrospectively collected and divided into training set (n = 149), test set (n = 38), and independent validation set (n = 39). Manual segmentation of tumor lesion was performed with ITK-SNAP, the ultrasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The texture features could quantify the spatial variation in the architecture and function of breast cancer, which are suitable to assess the information of tumor heterogeneity ( 20 , 34 ). The transform-filtered texture features could provide potential insight for quantifying tumor biological and multidimensional heterogeneity ( 6 , 11 , 30 , 36 ). Many studies had found that transform-filtered texture features were useful in predicting the tumor benignity and malignancy, lymph node metastasis, gene expression, and the efficacy of neoadjuvant chemotherapy ( 11 , 18 20 , 30 , 36 , 37 ), although some explanations of relationship between these complex features and tumor biology behavior remained to be elucidated ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The texture features could quantify the spatial variation in the architecture and function of breast cancer, which are suitable to assess the information of tumor heterogeneity ( 20 , 34 ). The transform-filtered texture features could provide potential insight for quantifying tumor biological and multidimensional heterogeneity ( 6 , 11 , 30 , 36 ). Many studies had found that transform-filtered texture features were useful in predicting the tumor benignity and malignancy, lymph node metastasis, gene expression, and the efficacy of neoadjuvant chemotherapy ( 11 , 18 20 , 30 , 36 , 37 ), although some explanations of relationship between these complex features and tumor biology behavior remained to be elucidated ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transform-filtered texture features could provide potential insight for quantifying tumor biological and multidimensional heterogeneity ( 6 , 11 , 30 , 36 ). Many studies had found that transform-filtered texture features were useful in predicting the tumor benignity and malignancy, lymph node metastasis, gene expression, and the efficacy of neoadjuvant chemotherapy ( 11 , 18 20 , 30 , 36 , 37 ), although some explanations of relationship between these complex features and tumor biology behavior remained to be elucidated ( 6 ). Some transform-filtered texture features from DBT and MRI could be incorporated as prediction model for the LVI status in breast cancer ( 6 , 11 ), since the transform-filtered features may be associated with the tumor complex microstructure, such as tumor cell proliferation, local necrosis, hemorrhage, inflammation, and microcalcifications, etc in LVI-positive tumor ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…considerable variation in case numbers (3872 and 20,625 [32,15] vs 188 and 186 cases [29,60]). Alternatively, the conflicting results could originate from unknown random or systematic differences between the internal and the validation data set.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Its diagnostic power is superior to that of experienced radiologists. Ren et al ( 49 ). aimed to explore machine learning-based ultrasomics in the preoperative noninvasive identification of hepatocellular carcinoma and intrahepatic cholangiocarcinoma.…”
Section: Application Of Conventional Radiomics In Intrahepatic Cholan...mentioning
confidence: 99%